Словoбразoвaтельныe особенности имен существительных общего рода (на матeриaлe русских гoвoров Литвы - Алексеева, Н. Т. (Kalbotyra, 1991)
The article under consideration is devoted to the analysis of the functions of the nouns signifying human beings without any distinction of their sex, namely, the words of common gender that are widely used in Russian dialects in Lithuania. First of all, we are interested in word-building peculiarities of this specific cathegory of words; secondly, we are interested in the productivity or lack of productivity; regularity or irregularity of the suffixes that help to build those words, and we also pay attention to a certain abundance of those words of common gender in Russian dialects spread in Lithuania.